ENSURING GENDER EQUALITY IN THE NEW UZBEKISTAN – THE BASIS OF A SUSTAINABLE FUTURE - Azamatova Gulmira Bayirbekovna (Research Focus International Scientific Journal, 2024)
This article talks about the importance of ensuring gender equality, significant work is being done in Uzbekistan to further strengthen the legal foundations of ensuring equality between women and men in all areas. Today, the issue of ensuring gender equality has risen to the level of state policy. This is considered one of the advanced steps in the field of human rights of our country.